First results with the neutron backscattering and TOF spectrometer option BATS on IN16B - Appel, Markus; Frick, Bernhard; Magerl, Andreas (Physica B-Condensed Matter, 2019)
We report on the status of the ongoing upgrade of the neutron backscattering spectrometer IN16B with the new BATS option, which enables operation of the instrument in inverted Time-of-Flight mode. First commissioning results are available, confirming the expectations and demonstrating its capabilities. Using Si 111 analysers, BATS allows to record neutron spectra with variable energy resolution down to 1.5 mu eV with momentum transfers up to 1.9 angstrom(-1), reaching energy transfers beyond - 600 mu eV and achieving a signal to noise ratio above 10(4).
CRIS-Team WoS Importer:2019-04-30